[RETRACTED] Analisis Metakognisi Peserta Didik dalam Pemecahan Masalah pada Materi Turunan - Maulidyawati, Desi; Irham, Muhammad (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2018)
[THIS ARTICLE HAS BEEN RETRACTED]Following a rigorous, carefully concerns and considered review of the article published in Kreano, Jurnal Matematika Kreatif-Inovatif to article entitled Ã¢â‚¬Å“Analisis Metakognisi Peserta Didik dalam Pemecahan Masalah pada Materi TurunanÃ¢â‚¬Â Vol 9, No 1, pp. 84-92, Juni 2018, DOI: 10.15294/kreano.v9i1.13125.The document and its content has been removed from Kreano, Jurnal Matematika Kreatif-Inovatif, and reasonable effort should be made to remove all references to this article.